The Effect of Increasing the Leadership of School Principals on the Performance of Education Staff in Wajo District - Sulfiani, Besse (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This research was conducted to find out: (1) the leadership of the heads of state vocational schools in Wajo district; (2) the performance of teaching staff at state vocational schools in Wajo district; and (3) whether there is a significant influence of principal leadership on the performance of state vocational education staff in Wajo district. The techniques used for data collection are documentation and questionnaires. The total population is 32 public vocational education staff in Wajo district. The collected data were processed using quantitative statistical analysis (percentage) and inferential statistical analysis (product-moment correlation) with a significance level of 5. The results of the data analysis showed that: (1) the leadership of the head of education at SMK Negeri in Wajo Regency is in a good category; (2) the performance of the State Vocational High School teaching staff in Wajo Regency is in the medium category; and (3) there is a significant influence of the principal's leadership on the performance of the State Vocational High School education staff in Wajo Regency.